Effects of environmental enrichment on ischemic tolerance - Farrell, Rosemarie, 1975- (2001)
Thesis (M.Sc.)--Memorial University of Newfoundland, 2002. Medicine Bibliography: leaves 72-92 In this study, we sought to determine whether environmental enrichment could alter the pattern of delayed CA1 cell death and functional impairment in a gerbil model of ischemic tolerance. Gerbils received either ischemic preconditioning. 5 minutes of ischemia or sham surgery. Three days after ischemia, gerbils were placed in either an enriched environment or standard laboratory housing. Animals were tested in an open field arena followed by two versions of a T-maze task. Following behavioural testing, extracellular CA1 field potential amplitudes and CA1 cell counts were determined. In open field testing (day 60), enriched, ischemic preconditioned and ischemic gerbils were not different than shams whereas, non-enriched, ischemic preconditioned and ischemic gerbils continued to have higher activity scores. Preconditioned and enriched ischemic animals learned the win-shift T-maze problem as quickly as shams, whereas, only the enriched preconditioned group acquired the win-stay paradigm. Surprisingly. CA1 cell counts were significantly lower in enriched versus non-enriched ischemic preconditioned animals. -- These data demonstrate that early, intensive intervention after ischemia can improve functional outcome but this is accompanied by increased brain damage.